Cylindrical Caved Space Stability Analysis for Extension Prediction of Mining-Induced Surface Subsidence. (27th May 2021) - Liu, Yang; Ge, Yongxiang; Zhang, Congrui; Ren, Fengyu; Ma, Junsheng; Ren, Gaofeng
Abstract : Subsequent extension of surface subsidence after vertical caving leads to large-scale surface destruction, as well as associated geological hazards. The extension prediction for cylindrical caved space, which appears circular surface subsidence, is still an intractable issue, due to the absence of robust models. To fill such a research gap, this paper provides an analytical model for the depth and orientation where the shear failure of isotropic rocks around the caved space is firstly observed. The anisotropy of surrounding rocks is further involved to enable this model to analyze the slip failure along discontinuities in anisotropic stress state. The prediction for the extension of the surface subsidence in Xiaowanggou iron mine is conducted, and the comparison between the prediction and the observation in satellite images demonstrates the validity of the proposed model. Even though this model cannot provide a definite boundary after extension, the prediction for the orientation surface subsidence extends to contribute to mitigating the effect of geological hazards. Another contribution of this work is to provide guidance to mitigate the impact of surface subsidence on safety and environment, such as filling the interspace between large-sized caved rocks by dumping small-sized waste rocks or backfilling the caved space with waste rocks.